Evaluation of Bioavailability of Residues of Pretilachlor in soil and Water under Paddy Cropping Condition and their In!uence on Lemna gibba - RajaRajeswari, Rathinasamy; Sathiyanarayanan, Sivanandam; Ramesh, Atmakuru; Ayyappan, Sornam (Journal of Agriculture and Environment, 2013)
Pretilachlor is a chloroacetanilide herbicide commonly used to control grasses, broadleaved weeds and floating aquatic species in transplanted and direct seeded rice. Herbicide residues lead to potential risk for aquatic plants and are extremely toxic to the aquatic ecosystem. Pretilachlor a chloroacetanilide herbicide, used in control of grasses, broadleaved weeds and floating aquatic species in transplanted and direct seeded rice. Herbicide residues lead to potential risk for aquatic plants and are extremely toxic to the aquatic ecosystem. The bioavailability and the toxicity of Pretilachlor residues on Lemna gibba was studied after applying the herbicide formulation at the recommended dose 1.25 g.a.i/ha under actual cropping conditions. The concentration of pretilachlor in paddy water and soil was analyzed by HPLC-UV method and its degradation products were confirmed by electrospray tandem mass spectrometry (LC-ESI -MS/MS) method. The recovery percentage at the limit of quantification (LOQ) 0.03 ppm was 92-102%. Residues in water dissipated rapidly with DT50 value 1.6 days and went to below detectable level by 15thday. The percentage inhibition of yield based on frond numbers was 97% at this time point, indicating toxicity index (TI) >1.0 to Lemna gibba. The observation recorded on 90th day showed no sign of inhibition of yield of Lemna gibba.